Threatened North African seagrass meadows have supported green turtle populations for millennia - de Kock, Willemien; Mackie, Meaghan; Ramsøe, Max; Allentoft, Morten E; Broderick, Annette C; Haywood, Julia C; Godley, Brendan J; Snape, Robin T E; Bradshaw, Phil J; Genz, Hermann; von Tersch, Matthew; Dee, Michael W; et al. (Proceedings of the National Academy of Sciences - PNAS, 2023)
is the second official aim of the current UN Ocean Decade (2021 to 2030) calling for the identification and protection of critical marine habitats. However, data to inform policy are often lacking altogether or confined to recent times, preventing the establishment of long-term baselines. The unique insights gained from combining bioarchaeology (palaeoproteomics, stable isotope analysis) with contemporary data (from satellite tracking) identified habitats which sea turtles have been using in the Eastern Mediterranean over five millennia. Specifically, our analysis of archaeological green turtle ( ) bones revealed that they likely foraged on the same North African seagrass meadows as their modern-day counterparts. Here, millennia-long foraging habitat fidelity has been directly demonstrated, highlighting the significance (and long-term dividends) of protecting these critical coastal habitats that are especially vulnerable to global warming. We highlight the potential for historical ecology to inform policy in safeguarding critical marine habitats.